2022
DOI: 10.7759/cureus.26666
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Smoking and Body Mass Index in Mortality Risk Assessment for Geriatric Hip Fracture Patients

Abstract: BackgroundSmoking, obesity, and being below a healthy body weight are known to increase all-cause mortality rates and are considered modifiable risk factors. The purpose of this study is to assess whether adding these risk factors to a validated geriatric inpatient mortality risk tool will improve the predictive capacity for hip fracture patients. We hypothesize that the predictive capacity of the Score for Trauma Triage in the Geriatric and Middle-Aged (STTGMA) tool will improve. MethodologyBetween October 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Patients were then stratified into risk quartiles based on the Score for Trauma Triage in the Geriatric and Middle Aged (STTGMA), a validated inpatient mortality risk assessment tool that has also shown efficacy in cost stratification. [5][6][7][8][9][10]12,13 Comparative analyses were conducted between high-risk quartiles (top 25% of patients based on the respective STTGMA score) for the prepandemic (October 2014 to January 2020) versus pandemic (February 2020 to January 2022) time periods and COVID1 versus COVID2 patients.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients were then stratified into risk quartiles based on the Score for Trauma Triage in the Geriatric and Middle Aged (STTGMA), a validated inpatient mortality risk assessment tool that has also shown efficacy in cost stratification. [5][6][7][8][9][10]12,13 Comparative analyses were conducted between high-risk quartiles (top 25% of patients based on the respective STTGMA score) for the prepandemic (October 2014 to January 2020) versus pandemic (February 2020 to January 2022) time periods and COVID1 versus COVID2 patients.…”
Section: Methodsmentioning
confidence: 99%
“…Previous work by this study group has investigated the Score for Trauma Triage in the Geriatric and Middle Aged (STTGMA), a validated risk-stratification tool for orthopaedic trauma patients. [4][5][6][7][8][9] Additional work by Konda et al 10 demonstrated the STTGMA tool's ability to adequately identify patients at high risk for poor outcomes, worse hospital quality measures, and higher costs of care. Therefore, this tool provides a platform to effectively identify patients at high risk for increased costs of care associated with their admission.…”
mentioning
confidence: 99%
“…Demographic features included age, body mass index, comorbidity profile as compiled by the Charlson comorbidity index (CCI), baseline ambulatory status, osteoporosis diagnosis (as determined by previous dual energy X-ray absorptiometry [DEXA] scan), and smoking status at the time of injury (current vs. not current). Additional recorded clinical data included the respective time from surgery to fixation failure, the Score for Trauma Triage in the Geriatric and Middle Aged (STTGMA), a validated tool for assessment of orthopedic trauma risk, and the Fracture Risk Assessment Tool (FRAX) tool for each patient 13 14 15 16 17) . The STTGMA score utilizes various clinical variables including demographic data (age, comorbidities), injury details (AIS [Abbreviated Injury Scale] for the head/neck and chest), and baseline functional status for determination of a mortality risk score.…”
Section: Methodsmentioning
confidence: 99%
“…As the original STTGMA tool utilized clinical data that is readily available on arrival to the emergency department, this study group continues to research additional accessible variables that may further improve our predictive capacity and refine the tool's efficacy. The original STTGMA tool included a patient's age and injury details, including the Abbreviated Injury Score (AIS) for the head/neck and chest, Glasgow Coma Scale (GCS), and comorbidity profile as defined by the Charlson Comorbidity Index (CCI) before additional research highlighted new variables such as a patient's baseline ambulatory status, American Society of Anesthesiologists (ASA) score, their COVID-19 status on hospital admission, baseline body mass index, smoking status at the time of injury, the season in which they sustain their injury [8][9][10][11][12]. More recently, STTGMA has become more adaptive to a patient's changing risk profile throughout their admission, now accounting for the occurrence of inpatient complications [13].…”
Section: Introductionmentioning
confidence: 99%